The influence of interleukin‐7 receptor α‐chain haplotypes on outcome after allogeneic hematopoietic cell transplantation. (29th October 2014) - Broux, B.; Shamim, Z.; Wang, T.; Spellman, S.; Haagenson, M.; Stinissen, P.; Ryder, L. P.; Müller, K.; Hellings, N.
Summary: We investigated the influence of IL‐7 receptor α ‐chain (IL‐7R α ) gene haplotypes in donors on the outcome of haematopoietic cell transplantation (HCT). Unlike the association between single donor SNPs and HCT outcome found previously, only trends towards association were found here, due to 'dilution' of SNPs into haplotypes.